Coordinating European Union environmental policy: Shifting from passive to active coordination - Andrew Jordan; Adriaan Schout; Anthony R Zito (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2004)
Environmental policy provides one of the oldest and most puzzling cases of policy coordination in the European Union (EU). The integration (or mainstreaming) of environmental objectives into non environmental policies such as agriculture, energy and transport, has a long history and commands high level political support among heads of state. However, the implementation of environmental policy integration (EPI) has not yet matched these ambitions. One of the main problems is that EPI has been seen as a macro problem of drafting sweeping statements and writing long term integration strategies. The need to embed EPI in micro policy processes i.e. the bottom-up formulation and implementation of EU policies in administrative settings has, however, mostly been ignored. This paper analyses the administrative coordination mechanisms at the micro-level within the Commission, the Netherlands and UK governments to gauge how fit they are to deliver on the EUs broader EPI objective. Using different theories of coordination, this paper concludes that all three have relied too heavily on setting long term coordination targets, without putting in place the administrative coordination (i.e. delivery) mechanisms. This paper concludes that the EUs macro approach (dubbed the Cardiff process) cannot perform effectively without the support of implementing actions at the micro level. At the same time, activities at the micro level need the political commitment expressed at the macro level. Moreover, environmental information needs to be transferred within and between the actors in a much more active manner so that environmental impacts can be designed out of policy proposals early on in the policy process. The conclusion of this study is that, in the face of greater interdependence between policies and the concomitant demand for greater policy coordination, passive coordination has had its day. But for many different reasons, the actors have not yet come to grips with what is required to implement active coordination.
Keywords: 330; coordination; environmental policy; environmental policy integration; European Union; governance; Internationale wirtschaftspolitische Koordination; EU-Staaten; EU-Umweltpolitik; Koordination